Up-to-Date Approach to Treatment of Inflammatory Infections in the Maxillofacial Region - M. G. Romantsov; M. A. Kovalevsky; A. I. Yaremenko; S. S. Grigoryan; A. L. Kovalenko (Антибиотики и Химиотерапия, 2020)
Cycloferon, a prospective interferon inductor, and the mechanism of its action were characterized. Its formulation for external use as liniment was developed. The pharmacotherapeutic effect of the drug in the treatment of paradontitis was shown. The drug efficacy in herpetic lesions of the mouth and lips mucosa was observed. The use of cycloferon in the treatment of the buccal mucosa affections in HIV-infected subjects was substantiated.